1978
DOI: 10.1080/17450397809428215
|View full text |Cite
|
Sign up to set email alerts
|

Die Wirkung der Reihenfolge von Grobfutter und Konzentraten in der Fütterung auf die Kohlenhydratverdauung und bakterielle Proteinsynthese im Pansen der Milchkuh

Abstract: In experiments with dairy cows provided with rumen fistulas and duodenal re-entrant canulas, the order of feeding roughage (chopped forage and pellets) and concentrates (maize and barley) was found to influence carbohydrate digestion and bacterial protein synthesis in the rumen. Feeding the roughage 90 min. before the concentrate caused a wider C2:C3 ratio and a sustained course of the pH-value (greater than 6.5) than the ratio other way round. This favoured cellulose digestion in the rumen when feeding choppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Adams (1985) suggested that shifting time of supplementation of grazing cattle from morning to afternoon increased forage intake through altered ingestive behavior. Voigt et al (1978) reporred that changing the feeding order of concentrate and forage portions of a diet (i.e., concentrates fed either before or after forages) was successful in manipulating ruminal fermentation patterns. The objective ofthis research was to determine if changing the time of supplementation from morning (coinciding with the first meal of the day) to afternoon (after the majority of a forage diet had been consumed) would affect forage intake, site and extent of nutrient digestibility, and ruminal pH.…”
mentioning
confidence: 99%
“…Adams (1985) suggested that shifting time of supplementation of grazing cattle from morning to afternoon increased forage intake through altered ingestive behavior. Voigt et al (1978) reporred that changing the feeding order of concentrate and forage portions of a diet (i.e., concentrates fed either before or after forages) was successful in manipulating ruminal fermentation patterns. The objective ofthis research was to determine if changing the time of supplementation from morning (coinciding with the first meal of the day) to afternoon (after the majority of a forage diet had been consumed) would affect forage intake, site and extent of nutrient digestibility, and ruminal pH.…”
mentioning
confidence: 99%
“…L'influence de l'ordre de distribution des aliments sur la digestion de l'azote dans le rumen est très peu documentée. Chez des vaches laitières, la distribution des concentrés 1 h 30 avant le fourrage aurait augmenté la synthèse microbienne (Voigt et al, 1978) mais également la dégradation de l'azote alimentaire de sorte que le flux azoté total n'était pas modifié.…”
unclassified